Transformasi Kondisi Sosial Ekonomi Pelaku Usaha Di Taman Nasional Alas Purwo Kabupaten Banyuwangi Pada Masa Pandemi Covid-19 - Dita Novita Dewi; Sunlip Wibisono; Fivien Muslihatinningsih (Jurnal Ekuilibrium, 2022)
Tourism is positioned as a crucial means of introducing culture and natural beauty in Indonesia. Currently, the tourism sector is considered to have an effective role in increasing the country's foreign exchange. The tourism sector is able to revive and prosper the economy of the surrounding community. This research was conducted in Alas Purwo National Park, Banyuwangi Regency. The purpose of this study was to find out how the impact of the Covid-19 pandemic on the socioeconomic conditions of business actors in Alas Purwo National Park. This research is a type of descriptive research using qualitative methods. Sources of data collected in the form of primary data and secondary data obtained through observation techniques, in-depth interviews, and documentation. Collecting information in this study using purposive sampling and snowball sampling. Data were analyzed by means of data reduction, data presentation, and drawing conclusions. The results of this study can be concluded that during the Covid-19 pandemic, it had an impact on the social conditions of business actors related to income levels and changes in types of work. During the Covid-19 pandemic, the income level of business actors decreased, and there was a change in the type of work from entrepreneurship to being farmers, ranchers, and even unemployment.